The Establishment of Fibrolytic Bacteria in the Foal Gastrointestinal Tract Is Related to the Occurrence of Coprophagy by Foals - Morgan Pyles; Miranda Agbana; Susan Hayes; Michael Flythe; Laurie Lawrence (Animals, 2023)
The consumption of maternal feces (coprophagy) is commonly observed in healthy foals and is a proposed contributor to microbial colonization of the foal’s gastrointestinal tract (GIT). This study investigated the role of coprophagy in the establishment of fibrolytic bacteria in the foal GIT. Nine thoroughbred mares were dosed with chromic oxide, an indigestible marker, as a method to detect the occurrence of coprophagy by their foals. Foal fecal samples were collected from 12 h to 21 d after birth to measure chromic oxide and neutral detergent fiber (NDF) and to enumerate cellulolytic bacteria using culture-based techniques. Milk yield was estimated at 7 and 14 d postpartum. Coprophagy was detected as early as 3 d after birth and detected in all foals by 7 d of age. There were strong relationships between coprophagy and cellulolytic bacteria and NDF in foal feces at 7 d of age (r = 0.9703 and r = 0.7878, respectively; p < 0.05). Fecal NDF and chromic oxide concentrations were negatively related to milk yield (r = –0.8144 and r = –0.6966, respectively; p < 0.05), suggesting milk availability affected the incidence of coprophagy. Based on the relationships identified, maternal feces are an important source of fiber and live microbes for the foal, contributing to the development of the microbial community.